Pengaruh Penambahan Kuning Telur Ayam Ras Dalam Bahan Pengencer Alami Air Buah Lontar Terhadap Kualitas Semen Babi Landrace Pada Suhu Preservasi 5°C - Winda Atika Tosi; Nancy Diana Frederika Katarina Foeh; Cynthia Dewi Gaina (Jurnal Veteriner Nusantara, 2021)
The quality of sperm an the supporting factors in the success of the process of insemination in boar. One of the cause of quality is the low temperature. The boar sperm have a thin plasma membrane so it can’t withstand low temperature. Needed ubstances that can protect the sperm from cold shock. The egg yolks with a lipoprotein content and lecithin are known to protect boar sperm stored at low temperature. The purpose of this study was to determine the effect of addition of egg yolks concentration 25%, 15% and 5% in palmyra juice diluents to improve the quality of the Landrace boar sperm. The research used is experimental method with Completely Randomized Design (RAL), each of 4 replications. Palmyra juice made by extraction method plus egg yolks, then addition of antibiotics. Palmyra juice diluents with different concentrations of egg yolks were added to the boar semen and stored by water jacket and non water jacket method. Evaluation of motility and percentage of live had performed microscopically. The results of this study were indicated that the addition of egg yolk as much as 25% with water jacket storage method is able to maintain the quality of sperm in a longer time compared with other concentrations. Motility up to 24 hours of storage with a 40,00±0,00% percentage and viability up to 30 hours of storage with 40.33±1.76% percentage.